Aspect ratio considerations for flat bottom hole defects in active thermography. Issue 1 (2nd January 2018) - Beemer, Maria Frendberg; Shepard, Steven M.
Abstract: Flaw detection capability of a Thermographic NDT system is often characterised using machined Flat-Bottom Holes (FBH) to simulate defects. For large diameter to depth (aspect) ratios, the FBH is typically indicated by the emergence of a localised hot spot in the IR image sequence. The FBH initially behaves identically to an extended adiabatic interface, allowing the centre-point depth to be determined using a one-dimensional model, before three-dimensional effects become dominant. However, for FBH with smaller aspect ratios, three-dimensional effects become dominant increasingly early, disrupting depth measurement using one-dimensional techniques. The dependence of these three-dimensional effects on aspect ratio is evident in the first and second logarithmic derivatives obtained through Thermographic Signal Reconstruction® (TSR®), when viewed using the Fourier number, and can be used to produce a simple model of FBH centre-point cooling behaviour. In both numerical modelling and experimental results, the maximum values of the logarithmic derivatives indicate the transition between one-dimensional adiabatic behaviour and the low aspect ratio regime, which occurs at an aspect ratio of 9. At aspect ratios below 9, the one-dimensional depth measurement accuracy decreases proportionally with aspect ratio and the composition of a flaw cannot be reliably determined from a single pixel.